Application Effect of PhET Virtual Laboratory and Real Laboratory on the Learning Outcomes of Class XI Students on Elasticity and Hooke's Law - Zulkifli Zulkifli; Azhar Azhar; Dina Syaflita (Jurnal Penelitian Pendidikan IPA, 2022)
Physics is a scientific field that studies a lot of abstract concepts which in the learning process demands a lot of ability to do mental depictions of something being studied. This study aims to describe the cognitive learning outcomes of students who apply PhET virtual laboratory and Real Laboratory on elasticity and Hooke's law. The subjects of this study were two classes totaling 70 students of class XI MIPA SMA Negeri 2 Pekanbaru. This research uses quasi-experimental research with a quantitative approach and tests (pre-test and post-test) as data collection methods. To analyze the data, several analyzes were used, namely descriptive analysis (Absorption Power, Learning Effectiveness and Normal Gain Test) and Inferential analysis (t-test). The results showed that the average value of the pre-test class that implemented the PhET virtual laboratory was 44.40 and the post-test score was 76.20, while the average value of the pre-test class that implemented the Real Laboratory was 43.80 and the score was 43.80, post-test was 84.20. The absorption category achieved by the two classes is in the same category, namely good and the effectiveness of the learning used is in the effective category. This shows that the learning outcomes of the two classes have increased with the average gain test being classified in the moderate criteria, namely 0.54 and 0.70. In summary, the use of PhET Virtual Laboratory and Real Laboratory has a significant effect on students' cognitive physics learning outcomes. PhET Virtual Laboratory and Real Laboratory are effective for teaching Elasticity and Hooke's Law as an alternative to physics experimental activities.